Hydroxyapatite synthesize from Pugilina cochlidium and Babylonia spirata, L shells as bone graft materials candidates in periodontics - Aini Hariyani Nasution; Rini Octavia Nasution; Desy Marlyn Situmorang; Andrie Harmaji (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
Hydroxyapatite has been widely used as bone graft materials in periodontics. However, hydroxyapatite is still considered costly, and many of them are imported. Hydroxyapatite manufacturers from natural sources could be an affordable alternative for periodontal regeneration therapy. Pugilina cochlidium and Babylonia spirata, L are the natural sources with high calcium carbonate. The two clamshells are easily found in Indonesia but their usage is still limited as hydroxyapatite materials. This study aims to synthesize the hydroxyapatite with sol-gel method from Pugilina cochlidium and Babylonia spirata, L as bone graft materials candidates.